POLIGAMI DALAM HUKUM ISLAM KONTEMPORER - Fatimatuzzahro Fatimatuzzahro (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
Practicing of polygamy gave effect on unharmonious and unbalance family, although polygamy from classical Islamic law it was permitted. Based on this problem, polygamy must be studies in depth by other approaches out of posifistic law in order to give better effect in making good family. This writing is delivering to find clear perspective about polygamy from inter-connective approach (inter-discipline perspective). This study used Islamic law (fiqh) approach, sociology, history and psychology. This research is used qualitative research and based on library research, which is analyzed from inter-connective approach. The finding of the research showed many perspective which is dominated to forbid polygamy, especially seeing from Islamic law, sociology, psychology and history. In addition, classical Islamic laws (fiqh) the only one make it longer for polygamy. Nevertheless, the effect f polygamy is unwell for family.